Preparation of 5-fluorouracil-loaded chitosan nanoparticles and study of the sustained release in vitro and in vivo - Li Sun; Yunna Chen; Yali Zhou; Dongdong Guo; Yufan Fan; Fangyan Guo; Yufeng Zheng; Weidong Chen (Elsevier, 2017)
The sustained-release properties of the biodegradable nano-drug delivery systems were used to improve the residence time of the chemotherapeutic agent in the body. These drug delivery systems were widely used to deliver chemotherapeutic drugs. The 5-fluorouracil loaded chitosan nanoparticles prepared in this paper have the above advantage. Here, we found that when the mass ratio of 5-fluorouracil and chitosan was 1:1, the maximum drug loading of nanoparticles was 20.13 ± 0.007%, the encapsulation efficiency was 44.28 ± 1.69%, the particle size was 283.9 ± 5.25 nm and the zeta potential was 45.3 ± 3.23 mV. The prepared nanoparticles had both burst-release and sustained-release phases in vitro release studies. In addition, the inhibitory effect of the prepared nanoparticles on gastric cancer SGC-7901 cells was similar to that of 5-fluorouracil injection, and the blank vector had no obvious inhibitory effect on SGC-7901 cells. In the pharmacokinetic study of rats in vivo, we found that AUC (0−t), MRT (0−t) and t1/2z of nanoparticles were significantly increased in vivo compared with 5-fluorouracil solution, indicating that the prepared nanoparticles can play a role in sustained-release.